EVALUATION OF CHEMICAL COMPOSITIONS OF RICE HUSK FROM LOCAL RICE SPECIES USING X-RAY FLUORESCENCE TECHNIQUE (FUDMA JOURNAL OF SCIENCES, 2023)
Rice husk is one of the main agricultural wastes in milling processes that is abundantly available in Nigeria. The research aim to evaluate the chemical composition of Bauchi State rice husk. The rice husk samples were collected in four Local Governments of Bauchi State and analyzed using X-Ray Fluorescence (XRF). Ten compounds were reveals in all the samples which are as follows; SiO, RbO, K2O, CaO, MnO, Fe2O3, NiO, CuO, ZnO, BrO and SrO. The major compounds having the trends SiO > K2O > CaO > Fe2O3 with mean values (in%) 4.7508, 0.4406, 0.24784 and 0.214625 for SiO, K2O, CaO and Fe2O3 respectively. Likewise, the minor compounds are in fractions which are; CuO, SrO, BrO, NiO, ZnO and MnO with their mean values (in%) 0.000303, 0.002325, 0.002858, 0.00514, 0.006532 and 0.021368 respectively. The high percentage of silica content in all the samples makes it of economic important in terms of industrial production. The trace compounds present are in minutes quantity and satisfy the condition of Federal Environmental Protection Agency, Nigeria (1998). The toxic and hazardous compounds were absents which minimize it risk to health in terms of industrial application within the environs.
Keywords: Compounds; XRF; Rice Husk; Silica